The application of equal channel angular pressing to join dissimilar metals, aluminium alloy and steel, using an Ag-Cu-Sn interlayer - Jafarlou, D.M.; Zalnezhad, E.; Ezazi, M.A.; Mardi, N.A.; Hassan, Mohamed Mohsen Abdel-Naeim (Elsevier, 2015)
Joining cylindrical and bar-shaped components manufactured from dissimilar materials is frequently required in various industrial applications. The current study focuses on developing equal channel angular pressing (ECAP) as a severe plastic deformation process for solid state joining of tubular aluminium alloy 6061 components and SAE 1018 steel rods. The influence of using a 0.1 mm thick 60Ag-30Cu-10Sn interlayer in addition to annealing at 220, 320,420 and 520 degrees C for 60 min is investigated as well. Finite element analysis (FEA) is performed in order to evaluate the deformation behaviour of the workpieces during the ECAP joining process. XRD and EDX analyses as well as nanoindentation and shear tests are carried out to evaluate the joints' characteristics. The FEA outcomes show remarkable accumulation of equivalent plastic strain with relatively low strain inhomogeneity. Moreover, the experimental results indicate that with increasing annealing temperature, joint strength exhibits improvement as well. It is also revealed that the application of an interlayer at any specific annealing temperature leads to achieving higher shear strength values. According to the results, shear strength of up to 32 MPa is feasible by having an interlayer and with subsequent annealing at 520 degrees C. (C) 2015 Elsevier Ltd. All rights reserved.